2020
DOI: 10.1002/adfm.202005328
|View full text |Cite
|
Sign up to set email alerts
|

2D Fabrication of Tunable Responsive Interpenetrating Polymer Networks from a Single Photoresist

Abstract: Light-induced curing of photoresists is a well-established technique to fabricate polymer networks with precise control over the material properties. Herein, control is exerted over network material properties of a single polymer blend through the spatiotemporally controlled incorporation of secondary polymer networks resulting in interpenetrating polymer networks (IPNs). Light gated control over materials properties of IPNs is assessed theoretically by applying the general rule of mixture and experimentally b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…[11][12][13] Relative to UV light, visible light is naturally abundant, less expensive, and benign (generally reduced absorption and scattering), which gives it the potential to advance 3D printing of polymeric materials by enabling economical preparation of, for example, cell-laden hydrogels, [14] opaque composites, [15] or multimaterial structures (via wavelength selective reactions). [7,[16][17][18][19] Recently, we demonstrated that a three component photosystem comprising a visible-light-absorbing photoredox catalyst (PRC) with donor (diphenyliodonium) and acceptor (triphenyl (n-butyl) borate) co-initiators could facilitate photocuring of acrylate-based resins on timescales (approximately seconds) that were competitive with commercial UV light systems (Figure 1). [11] However, the difference in mechanism undergone by UV photoinitiators (PIs) (Type I) and visible PRCs (Type II) to generate reactive radicals results in greater oxygen sensitivity for the latter.…”
mentioning
confidence: 99%
“…[11][12][13] Relative to UV light, visible light is naturally abundant, less expensive, and benign (generally reduced absorption and scattering), which gives it the potential to advance 3D printing of polymeric materials by enabling economical preparation of, for example, cell-laden hydrogels, [14] opaque composites, [15] or multimaterial structures (via wavelength selective reactions). [7,[16][17][18][19] Recently, we demonstrated that a three component photosystem comprising a visible-light-absorbing photoredox catalyst (PRC) with donor (diphenyliodonium) and acceptor (triphenyl (n-butyl) borate) co-initiators could facilitate photocuring of acrylate-based resins on timescales (approximately seconds) that were competitive with commercial UV light systems (Figure 1). [11] However, the difference in mechanism undergone by UV photoinitiators (PIs) (Type I) and visible PRCs (Type II) to generate reactive radicals results in greater oxygen sensitivity for the latter.…”
mentioning
confidence: 99%
“…Distinguished from other multipolymer combinations, IPNs are stable in solvents with suppressed creep and flow [ 147 ] and are thus suitable for biomedical applications, damping materials, tough and impact-resistant materials, etc. Some examples include light-gated control [ 148 ], greener extraction [ 149 ], increased robustness [ 150 ] and organic photovoltaic inks [ 151 ].…”
Section: Overview Of Intelligent Polymer-based Applications In Multiple Fieldsmentioning
confidence: 99%
“…Our group has pioneered the concept of wavelength orthogonal reactions in soft matter materials. [ 34–38 ] In particular, one of the systems contains a styrylpyrene group, which can undergo dimerization by visible light (405 nm) and dissociation by UV light. [ 36,39 ] Styrylpyrene can be applied in conjunction with an acrylamidylpyrene, having a highly redshifted activation wavelength of up to 490 nm.…”
Section: Introductionmentioning
confidence: 99%